Muhammad Anwar Sadat and Soviet-Egyptian Relations in Mid-1950s — Early 1970s: Memoirs of Soviet and Egyptian Politicians - V. P. Podolnikov; N. A. Lagoshina (Научный диалог, 2023)
The Soviet-Egyptian relations from the mid-1950s to the early 1970s are analyzed through the prism of their perception by Soviet and Egyptian politicians and diplomats. The ideological, political and world views of the second Egyptian President Anwar Sadat are shown, which predetermined the turn of Egypt’s foreign policy from cooperation with the USSR to an alliance with the USA. Subsequently publishing his “Autobiography”, Sadat hoped to use it as a tool in solving current political problems, in particular, as a means of substantiating the turn he had made. The argumentation and methods of implementing a new direction in Egypt’s foreign policy are disclosed. The details of the behind-the-scenes game of politicians, which are not reflected in the official diplomatic documentation, are highlighted. The real picture of negotiations and discussions of delicate diplomatic topics at the highest level is being reconstructed. The memoirs reflect the political and social atmosphere of Egyptian society at a turning point in the history of this country. They most clearly trace the influence of the “human factor” on the adoption of certain political decisions. Numerous characteristics of the Soviet and Egyptian partners in the negotiation process are given. Comparison of memoir sources allows us to get as close as possible to the reliable history of Soviet-Egyptian relations of that time.